Panchakarma : ayurveda's mantra of rejuvenation - Reghunath, N.; Kumar, Anil K.; Invis Multimedia Trivandrum, India; Kerala (India) : Department of Tourism (Thiruvanthapuram, Kerala : Invis Multimedia, 2003)
About the panchakarma i.e. rejuvenation therapy of Ayurveda that practiced in Kerala.This book intends to introduce the various rejuvenation therapies practiced in Panchakarma. Practice of themse therapies should always be done under the able guidance of qualified and competent physicians and trained attendants
Published in association with the Department of Tourism, Government of Kerala
Keywords: Therapeutics -- Kerala -- India; Medicine, Ayurvedic